2015
DOI: 10.1007/s12311-015-0669-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Immune Activation Produces Cerebellar Hyperplasia and Alterations in Motor and Social Behaviors in Male and Female Mice

Abstract: There have been suggestions that maternal immune activation is associated with alterations in motor behavior in offspring. To explore this further, we treated pregnant mice with polyinosinic:polycytidylic acid (poly(I:C)), a viral mimetic that activates the innate immune system, or saline on embryonic days 13-15. At postnatal day (P) 18, offspring cerebella were collected from perfused brains and immunostained as whole-mounts for zebrin II. Measurements of zebrin II+/- stripes in both sexes indicated that pren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 148 publications
(169 reference statements)
1
22
1
1
Order By: Relevance
“…A reduction in Purkinje cell number was detected after induction of MIA with influenza virus or Poly(I:C) at GD9.5 in mice (Shi et al, 2009) and with Escherichia coli injections in rats (GD17) (Wallace et al, 2010), similar to the cerebellar Purkinje cell defects observed in postmortem samples of patients with ASD . In contrast, MIA induction in mid-gestation (GD13-15) with Poly(I:C) results in an increase in Purkinje cell numbers in juvenile and adult mice (Aavani et al, 2015). This may represent a narrow window in which inflammatory cytokines enhance proliferation or inhibit apoptosis of Purkinje cell precursors.…”
Section: Developmental Dynamicsmentioning
confidence: 97%
“…A reduction in Purkinje cell number was detected after induction of MIA with influenza virus or Poly(I:C) at GD9.5 in mice (Shi et al, 2009) and with Escherichia coli injections in rats (GD17) (Wallace et al, 2010), similar to the cerebellar Purkinje cell defects observed in postmortem samples of patients with ASD . In contrast, MIA induction in mid-gestation (GD13-15) with Poly(I:C) results in an increase in Purkinje cell numbers in juvenile and adult mice (Aavani et al, 2015). This may represent a narrow window in which inflammatory cytokines enhance proliferation or inhibit apoptosis of Purkinje cell precursors.…”
Section: Developmental Dynamicsmentioning
confidence: 97%
“…Later assessments of social behavior in MIA mouse offspring have relied heavily upon on simplistic, automated tools, such as the three-chamber social approach test to quantify sociability as indexed by a preference for a social versus a nonsocial stimulus (64). Several laboratories have now reported that mice exposed to PolyIC challenge during gestation fail to demonstrate species typical preferences for the social stimulus when evaluated in adolescence or adulthood (60, 62, 63, 65-72), though deficits may be strain specific (61). Only a small number of studies have evaluated the effects of MIA on complex, reciprocal social interactions.…”
Section: Assessing Validity Of the Mia Modelmentioning
confidence: 99%
“…Besides post--pubertal synaptic deficits, the delayed onset of prenatal poly(I:C)--induced deficits in PPI may also involve altered functional maturation of the subcortical dopamine system Vuillermot et al, 2010), brain volumetric changes throughout adolescence (Piontkewitz et al, 2011), and altered maturation of prefrontal GABAergic systems (Richetto et al, 2014). It should also be noted that prenatal poly(I:C)--induced immune activation can lead to various behavioral and neuronal abnormalities with early juvenile or adolescent onsets, including hypersensitivity to dopamine--stimulating psychotomimetic drugs (Meyer et al, 2008,;Vuillermot et al, 2010), cognitive deficits , impairments in social interaction (Aavani et al, 2015), and deficits in hippocampal neurogenesis . Hence, whereas the present findings may be more important for neuropsychiatric disorders with adult onsets, prenatal immune activation models are generally also relevant for neurodevelopmental disorders that are characterized by overt symptomatology in childhood or early adolescence.…”
mentioning
confidence: 99%